(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the effect of metformin on the clinical presentation and metabolic disturbances of polycystic ovary syndrome. Study Design: Observational study. Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gyneacology Unit-I, Sandeman Provincial Hospital, Bolan Medical College, Quetta from 09-09-2018 to 06-06-2019 Materials and Methods: Fifty patients with clinical signs and symptoms of polycystic ovaries syndrome attending the OPD of department of obstetrics and gyneacology Unit-I, Sandeman provincial hospital, Bolan medical college Quetta. Results: A total of fifty women with Polycystic Ovary Syndrome were included in the study. The average age of the patients was found 26.46 + 1.40 (95% CI: 23.64 to 29.28) years. The signs and symptoms, of Acne was present in 33 patients (66 %), Hirsutism was present in 43 patients (86 %), Menstrual Irregularity was present in all patients (100 %), Obesity was present in 28 patients (56 %) and Infertility was present in 37 patients (74 %), were present in the patients before treatment. Improvement in the signs and symptoms, of Acne was seen in 2 patients (6.06 %), Hirsutism was seen in 2 patients (4.65 %), Menstrual Irregularity was seen in 13 patients (26 %), Obesity was seen in 4 patients (5.40 %) and Infertility was seen in 2 patients (5.40 %), after 3 months’ treatment. Improvement in the signs and symptoms, of Acne was seen in 5 patients (15.15 %), Hirsutism was seen in 6 patients (13.95 %), Menstrual Irregularity was seen in 34 patients (68 %), Obesity was seen in 12 patients (42.85 %) and Infertility was seen in 5 patients (13.51 %), after 6 months’ treatment. Conclusion: Metformin administration to women who have signs and symptoms of polycystic ovarian syndrome is associated with marked improvement in menstrual irregularity resulting in regular menstrual cycles and achievement of pregnancy. Improvement in other signs and symptoms of PCOS was also seen with administration of Metformin for six months.